Numerical analysis of particle flows within a double expansion - Love, A.I.J.; Giddings, D.; Power, H. (Elsevier, 2014)
The effect of solid particles within flows having zones of recirculation is of interest in pulverised fuel distribution and combustion at burners. Previous modelling of a 1/4 scale test rig was performed by Giddings et al. (2004), and an instability was later identified within the domain. Subsequently the transient dynamics of the flow of air through a double expansion were investigated numerically and a recirculation zone was found to develop at one of the four corners of the expansion. In the work presented here the flow of solid particles through this double expansion is investigated using the commercial software ANSYS FLUENT R14.0. The Stress-Omega Reynolds Stress Model is used to model the gas phase turbulence and the Discrete Particle Model is used to model the solid particle flow. The dynamics of the flow are reported here for 10 μm and 60 μm particles and for mass loadings from 0 to 1 kgparticles/kgair. The simulations show a distinct transition to a vortex shedding type instability with the addition of the discrete phase. Furthermore, for increasing mass loading and particle Stokes number the Coanda effect is reduced leading to two large recirculation zones in opposing corners of the domain. The characteristics of the flow field are in qualitative agreement with studies of particle flows in jet flows and shear layers. This work serves to highlight some of the challenges in modelling complex pneumatic conveying flows from an industrial perspective.